Consistent SMARCB1 homozygous deletions in epithelioid sarcoma and in a subset of myoepithelial carcinomas can be reliably detected by FISH in archival material. Issue 6 (3rd March 2014) - Le, Francois; Zhang, Lei; Fletcher, Christopher D.; Ribeiro, Agnes; Singer, Samuel; Italiano, Antoine; Neuville, Agnes; Houlier, Aurélie; Chibon, Frederic; Coindre, Jean‐Michel; Antonescu, Cristina R.
<x xml:space="preserve">Abstract</x> Epithelioid sarcomas (ES) are mesenchymal neoplasms subclassified into distal and proximal subtypes based on their distinct clinical presentations and histologic features. Consistent loss of SMARCB1 nuclear expression has been considered as the hallmark abnormality for both subtypes, a feature shared with atypical teratoid/rhabdoid tumor of infancy (ATRT). While virtually all ATRTs harbor underlying SMARCB1 somatic or germline alterations, mechanisms of SMARCB1 inactivation in ES are less well defined. To further define mechanisms of SMARCB1 inactivation a detailed molecular analysis was performed on 40 ES (25 proximal and 15 distal ES, with classic morphology and negative SMARCB1 expression) for their genomic status of SMARCB1 and related genes encoding the SWI/SNF subunits (PBRM1, BRG1, BRM, SMARCC1/2 and ARID1A) by FISH using custom BAC probes. An additional control group was included spanning a variety of 41 soft tissue neoplasms with either rhabdoid/epithelioid features or selected histotypes previously shown to lack SMARCB1 by IHC. Furthermore, 12 ES were studied by array CGH (aCGH) and an independent TMA containing 50 additional ES cases was screened for Aurora Kinase A (AURKA) and cyclin D1 immunoexpression. Homozygous SMARCB1 deletions were found by FISH in 36/40 ES (21/25 proximal‐type). One of the distal‐type ES displayed homozygous SMARCB1 deletion in the tumor cells, along with a heterozygous deletion within normal tissue, finding confirmed by array CGH. None of the proximal ES lacking homozygous SMARCB1 deletions displayed alterations in other SWI/SNF subunits gene members. Among controls, only the SMARCB1‐immunonegative myoepithelial carcinomas displayed SMARCB1 homozygous deletions in 3/5 cases, while no gene specific abnormalities were seen among all other histologic subtypes of sarcomas tested regardless of the SMARCB1 protein status. There was no consistent pattern of AURKA and Cyclin D1 expression. The array CGH was successful in 9/12 ES, confirming the SMARCB1 and other SWI/SNF genes copy numbers detected by FISH. Our study confirms the shared pathogenesis of proximal and distal ES, showing consistent SMARCB1 homozygous deletions. Additionally we report the first ES case associated with a SMARCB1 constitutional deletion, establishing a previously undocumented link with ATRT. Alternative mechanisms of SMARCB1 inactivation in SMARCB1‐disomic ES remain to be identified, but appear unrelated to large genomic abnormalities in other SWI/SNF subunits. © 2014 Wiley Periodicals, Inc.